Salmonella typhi endocarditis: a case report. Issue 10 (26th September 2003) - Khan, G Q; Kadri, S M; Hassan, G; Shahid, I T; Gazanfar, A; Kak, M; Showkat, H
Abstract : Salmonella are a rare cause of infective endocarditis. This report describes a case where Salmonella typhi was isolated from the blood and urine of a patient with echocardiographically documented aortic valve disease and endocarditis. The patient was treated with two weeks of ceftriaxone (3 g/day) and amikacin (15 mg/kg/day), followed by a further two weeks of ceftriaxone (3 g/day) alone. He made a complete recovery.